Domestic Violence and Mental Health: The Experience of Workers in Domestic Violence Shelters - Migneault, Michelle (Université d'Ottawa | University of Ottawa, 2018)
This qualitative research project focuses on mental health in female victims of domestic violence. More specifically, it looks at 1) shelter workers’ perspectives on women who experience both domestic violence and mental health problems; 2) the approaches used when working with these women; and 3) the challenges workers face in their work with these women, as well as possible solutions to overcome these challenges. Data was collected by interviewing four workers in two domestic violence shelters in Ottawa. The research participants had between one and ten years experience working in shelters. The results demonstrate that, according to the shelter workers, women who experience domestic violence also experience a significant amount of mental health problems, including anxiety and depression, and women who experience both domestic violence and mental health problems tend to require more time and attention from the workers. The approaches used by the workers vary significantly, with a trauma-informed approach being the most common. Moreover, according to the participants, obtaining a diagnosis can open the door for multiple services. Furthermore, not being experts in mental health and women’s substance use were reported as the most important challenges they face when working with this population. Other challenges included not having enough staff, working with aggressive or violent women, and feeling powerless when working with women experiencing mental health problems. Several structural challenges were also identified, such as the lack of affordable housing in Ottawa, problematic laws regarding violence against women, and the long waiting list for mental health services, which prevent women from successfully transition to living independently in the community. Keywords: Domestic violence, domestic violence shelter, mental health, substance use, intervention approaches